Blonde Indian : An Alaska Native Memoir - Hayes, Ernestine, 1945- (Book collections on Project MUSE., 2006)
We witness her struggles alongside other Tlingit men and women - many of whom never left their Native community but wrestle with their own challenges, including unemployment, prejudice, alcoholism, and poverty." "The author's personal journey, the symbolic stories of contemporary Natives, and the tales and legends that have circulated among the Tlingit people for centuries are all woven together, making Blonde Indian much more than the story of one woman's life. Filled with anecdotes, descriptions, and histories that are unique to the Tlingit community, this book is a document of cultural heritage, a tribute to the Alaskan landscape, and a testament to how going back - in nature and in life - allows movement forward."--Jacket